Special forces innovation : how DARPA attacks problems - Dugan, Regina E. (2013)
Aims to demonstrate that the Pentagon's Defence Advanced Research Projects Agency's (DARPA's) approach to breakthrough innovation is a viable and compelling alternative to the traditional models common in large, captive research organisations.